Ventral Longitudinal Intraspinal Fluid Collection in Patients with Cervical Disc Herniation: A Report of Two Cases - Rui Hirasawa; Takashi Itabashi; Tsuneji Kita; Chikato Mannoji (Case Reports in Orthopedics)
We encountered two cases of cervical disc herniation, wherein cerebrospinal fluid collection in the ventral epidural space between the cervical spine and the thoracic spine was noted. The patients, two women aged 71 and 43 years, were diagnosed with cervical disc herniation and underwent anterior cervical discectomy and fusion. Unexpected cerebrospinal fluid leakage was observed prior to exposure of the dura mater. Notably, the dura mater was intact following the removal of the herniated disc in both cases. No cerebrospinal fluid leakage symptoms were observed, and relief from the neurological symptoms related to the cervical disc herniation was observed in both cases following the surgery. Findings of preoperative magnetic resonance imaging and computed tomography myelography were carefully reviewed, retrospectively. Both patients presented with similar features including expansion of cerebrospinal fluid collection in the ventral epidural space between the cervical spine and the thoracic spine. These observed features were similar to those of superficial siderosis, which is a form of duropathy—a disease caused by dural defects. Therefore, the patients in this case study might have a subclinical duropathy with associated cervical disc herniation.